THE ANTIRHEUMATIC ACTIVITY OF MUNTINGIA CALABURA L. LEAVES ETHANOL EXTRACT AND ITS FRACTION - Sarimanah, Jamilah; I, Ketut Adnyana; Sukandar, Elin Yulinah; Kurniati, Neng Fisheri (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Rheumatoid arthritis is chronic inflammation disorder that can be treated with anti-inflammatory drug such as methylprednisolone. Several medicinal plants shave the potential to be used in arthritis therapy, one of which is Muntingia calabura L. The objective of this research was to study the antirheumatic activity of M. calabura leaves ethanol extract and its n-hexane, ethyl acetate, and water fractions in a rheumatoid arthritic rat model. Methods: Rheumatoid was induced in rats by intraplantar injection of Complete Freund's Adjuvant (CFA) into the right foot paw of Wistar rats. The paw volume was measured by a plethysmometer. The histology of right foot paw was carried out. For chronic CFA inflammation, induced paw edema assay was used, whereas chronic inflammation was assessed by CFA induced arthritis. The histopathology of synovial joints (paw) was carried out. Result: The results of the study revealed that in CFA-induced arthritic rats, methylprednisolone, M. calabura ethanol extract, and its fractions were able to reduce inflammation. Histopathology examination also showed a reduction of in cartilage destruction, influx of inflammatory cells, pannus formation, fibrin deposition, and synovitis. Conclusion: M. calabura L. n-hexane fraction showed a better anti-rheumatic activity in rats among other fractions. Keywords: Muntingia calabura L. leaves, Ethanol extract, N-hexane fraction, Ethyl acetate fraction, Antirheumatic. Â